Investigating the Link between Smoking and Cognitive Function in Elderlies (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: As we age, our cognitive abilities can decline, making everyday tasks more challenging. This decline is often linked to health behaviors throughout life. By adopting healthy habits in youth and adulthood, we may be able to improve our cognitive function later in life and reduce the risk of cognitive impairment.Objective: This study specifically investigates whether smoking, a common habit, has a negative impact on the cognitive function of older adults.Methods: This cross-sectional study was conducted among 120 elderly adults aged 60 years or above residing in Savar Upazila, Dhaka from July to September 2023. respondents were included by convenience sampling method. Data were collected by face-to-face interview with a semi- structured questionnaire where cognitive functional status was observed through MMSE (Mini-Mental State Examination) scale and their smoking status was also recorded.Results: Over half of the participants (55.8%, n=67) reported using tobacco, with smoking (34.2%, n=41) being more prevalent than smokeless tobacco use (21.7%, n=26). Interestingly, the majority of tobacco users (31.7%, n=38) had a long history of consumption, exceeding 21 to 50 years. Smokers had a significantly higher prevalence of mild cognitive impairment (35.8%) compared to non- smokers (13.2%). The study revealed statistically significant relationship (p